IT Governance Evaluation of Hotel Warehouse Section Using the COBIT 5 Framework - Surya Pramana, I Wayan; Risanti Iswardani, Putu; Arya Mertasana, Putu (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
The warehouse section of a hotel requires good IT governance support to ensure operational activities in the warehouse run smoothly, especially in matters relating to IT Resource (Hardware, Software and Infrastructure). So that to ensure IT governance in the warehouse of a hotel has been running well or not, it is necessary to evaluate the IT governance. Based on that, the purpose of this research is to evaluate IT governance in the warehouse section of a hotel. Evaluation is carried out by an audit process to assess the maturity of IT governance through calculation of capability levels using the COBIT 5 framework on the Delivery, Service and Support (DSS) domains. The research was conducted in a case study at Mercure Bali Nusa Dua Hotel with the conclusion that the level of IT governance capabilities in the warehouse section at Mercure Bali Nusa Dua Hotel is at the level of Managed Process with capability level 2.5, which indicates that IT governance in the Mercure Bali Nusa Dua Hotel warehouse section has been well managed in terms of planning, supervision and control of IT services. Recommendations are given in accordance with the audit results with hope that the company can achieve the expected capability level by making improvements to IT processes that have the greatest capability gap